En casa: experiencia gastronómica (2020)
This document contains the process of development of En Casa thesis. The project is based on a service design that allows a person as a client or diner to create, live and experiment a gastronomic experience at home memorable in all of it's components. In this way, En Casa seeks to offer the experience adapted to the new context and reality as a consequence of the 2020 Pandemic (COVID-19). A gastronomic experience involves actions, activities and situations that are executed before-during-after the experience which go further from the fact than just eating. In general, people give them a huge importance. This is why going out to dinner becomes a social activity within a gastronomic experience. So taking into account that the quarantine period didn't allow people to go out (generating uncertainty and risk of contagion) the service design consists on bringing every detail/component of a gastronomic experience to home. All of the actions, activities and situations occurring in a gastronomic experience can be brought into this space.